Taxonomy and Biogeography of New World Quail - R. J. Gutierrez (National Quail Symposium Proceedings, 2017)
New World quail are a distinct genetic lineage within the avian order Galliformes. The most recent taxonomic treatment classifies the group as a separate family, Odontophoridae, within the order. Approximately 31 species and 128-145 subspecies are recognized from North and South America. Considerable geographic variation occurs within some species which leads to ambiguity when describing species limits. A thorough analysis of the Galliformes is needed to clarify the phylogenetic relationships of these quail. It is apparent that geologic or climatic isolating events led to speciation within New World quail. Their current distribution suggests that dispersal followed speciation. Because the genetic variation found in this group may reflect local adaption, the effect of translocation and stocking of pen-reared quail on local population genetic structure must be critically examined.
Keywords: biogeography; New World quail; Odontophoridae; taxonomy